Analysis of composite plates using a layerwise theory and a differential quadrature finite element method. (15th November 2016) - Liu, Bo; Ferreira, A.J.M.; Xing, Y.F.; Neves, A.M.A.
Abstract: A layerwise shear deformation theory for composite laminated plates is discretized using a differential quadrature finite element method (DQFEM). The DQFEM is a weak-form differential quadrature method that can provide highly accurate results using only a few sampling points. The layerwise theory proposed by Ferreira is based on an expansion of Mindlin's first-order shear deformation theory in each layer and results for a laminated plate with three layers were presented as example in the original paper. This work generalized the layerwise theory to plates with any number of layers. The combination of the DQFEM with Ferreira's layerwise theory allows a very accurate prediction of the field variables. Laminated composite and sandwich plates were analyzed. The DQFEM solutions were compared with various models in literature and especially showed very good agreements with the exact solutions in literature that was based on a similar layerwise theory. The analysis of composite plates based on Ferreira's layerwise theory indicates that the DQFEM is an effective method for high accuracy analysis of large-scale problems.